A functional analysis of the DNA glycosylase activity of mouse MUTYH protein excising 2-hydroxyadenine opposite guanine in DNA - Ushijima, Yasuhiro (Oxford University Press, 2005)
2-Hydroxy-2-deoxyadenosine triphosphate (2-OH-dATP), generated by the oxidation of dATP, can be misincorporated by DNA polymerases opposite guanine in template DNA during DNA replication, thus causing spontaneous mutagenesis. We demonstrated that mouse MUTYH (mMUTYH) has a DNA glycosylase activity excising not only adenine opposite 8-oxoguanine (8-oxoG) but also 2-hydroxyadenine (2-OH-A) opposite guanine, using purified recombinant thioredoxin-mMUTYH fusion protein. mMUTYH formed a stable complex with duplex oligonucleotides containing an adenine:8-oxoG pair, but the binding of mMUTYH to oligonucleotides containing a 2-OH-A:guanine pair was barely detectable, thus suggesting that mMUTYH recognizes and interacts with these two substrates in a different manner which may reflect the difference in the base excision repair process for each substrate. Mutant mMUTYH with G365D amino acid substitution, corresponding to a G382D germline mutation of human MUTYH found in familial adenomatous polyposis patients, almost completely retained its DNA glycosylase activity excising adenine opposite 8-oxoG; however, it possessed 1.5% of the wild-type activity excising 2-OH-A opposite guanine. Our results imply that the reduced repair capacity of the mutant hMUTYH(G382D), which inefficiently excises 2-OH-A opposite guanine, results in an increased occurrence of somatic G:C to T:A transversion mutations in the APC gene as well as tumorigenesis in the colon.